The Effect of Metformin on Ethanol- and IndomethacinInduced Gastric Ulcers in Rats - İpek, Betül Esra and Yüksel, Meral and Cumbul, Alev and Ercan, Feriha and Cabadak, Hülya and Aydın, Banu and Alican, İnci (Turkish Journal of Gastroenterology, 2022)
Background: Previous studies found metformin as an effective agent to suppress oxidative stress, inflammation, and apoptosis in various inflammatory diseases. The present study investigated the effect of metformin against 2 experimental gastric injury models in rats, using macroscopical, histopathological, biochemical, and immunostaining studies. Methods: After 24 hours of fasting, male Sprague-Dawley rats (280-400 g) (n = 8 per group) received indomethacin (80 mg/kg; indo ulcer group) or absolute ethanol (5 mL/kg; ethanol ulcer group) or vehicle orally by gavage. Metformin (500 mg/kg) was given orally for 3 days prior to indomethacin or ethanol challenge. Ranitidine (50 mg/kg) was given orally for 3 days before indomethacin or ethanol administration as a positive control. On day 3, the animals were euthanized 6 hours after indo or 1 hour after ethanol challenge. Gastric samples were used for macroscopic scoring, histopathological examinations, and biochemical assays. Trunk blood was collected for the assessment of interleukin-1β level. Results: In both ethanol ulcer and indo ulcer groups, metformin decreased the extent of gastric lesions macroscopically and microscopically, improved the high chemiluminescence levels, and the percentage of terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive apoptotic cells compared with untreated ulcer groups. Gastric blood flow analysis revealed significant increases in both metformin-treated ulcer groups compared to untreated ulcer groups. Conclusion: The findings of the present work demonstrated the gastroprotective effect of metformin against the development of gastric mucosal lesions induced by ethanol and indomethacin in non-diabetic, normoglycemic rats via its antioxidant and anti-apoptotic properties and partly from its ability to restore blood flow Cite this article as: İpek BE, Yüksel M, Cumbul A, et al. The effect of metformin on ethanol- and indomethacin-induced gastric ulcers in rats. Turk J Gastroenterol. 2022;33(9):767-776.